2022
DOI: 10.7717/peerj.14089
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of the reliability and quality of Youtube videos as a source of information on health-related post-COVID pain

Abstract: Background The use of the internet as a source of information has increased during the pandemic, and YouTube has become an increasingly important source of information on Coronavirus disease 2019 (COVID-19). In the long COVID picture, which occurs when symptoms related to COVID-19 last longer than 1 month, pain involving the musculoskeletal system affects the quality of life quite negatively. The aim of this study was to investigate the informational value and quality of YouTube videos related to post-COVID pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…15 This may reflect increasing demand and Internet usage over time. [6][7][8][9] This study found that the majority of centers (79.7%) were updated in the year of 2022. The remaining websites were updated recently, with the latest date listed as 2019.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…15 This may reflect increasing demand and Internet usage over time. [6][7][8][9] This study found that the majority of centers (79.7%) were updated in the year of 2022. The remaining websites were updated recently, with the latest date listed as 2019.…”
Section: Discussionmentioning
confidence: 80%
“…6,7 This has been further impacted by the COVID-19 pandemic, where social media and Internet search engines have been further utilized to seek health information. 8,9 Pediatric craniofacial anomalies are deformities that affect head and facial bones. 10 Cleft lip and palate occurs in nearly 1 in 600 live births.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, digital video, as an important carrier of information, has been widely used in patients' education. In otorhinolaryngology, YouTube and/or TikTok content has been investigated for the educational value of videos about cholesteatoma [9], pediatric tonsillectomy [10], middle ear ventilation tubes [10], rhinoplasty [12], tinnitus [13], and thyroid cancer [4,14,15]. Yet, the quality evaluation of videos related to laryngeal cancer remains absent.…”
Section: Principal Ndingsmentioning
confidence: 99%
“…Although initially designed as a tool for written information, DISCERN has been applied as a scoring test for grading the quality of videos in previous research. 2,6,34,36 DISCERN scores are interpreted as excellent (63-75), good (51-62), fair (39-50), poor (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), and very poor (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Video Scoringmentioning
confidence: 99%